Serial cytokine levels in patients with severe sepsis - Wu, Huang-Pin; Chen, Chian-Kuang; Chung, Kong; Tseng, Jo-Chi; Hua, Chung-Ching; Liu, Yu-Chih; Chuang, Duen-Yau; Yang, Chung-Han (Inflammation research, 2009)
Objective and design The serial or dynamic changes of cytokine levels in severely septic patients, between shock and no shock, survivors and non-survivors are still unclear. Methods Seventy-six patients with severe sepsis were enrolled to our study. Plasma levels of interferon-γ, interleukin (IL)-6, IL-10, IL-12 and transforming growth factor-β1 from day 1 to day 7 were determined. Results IL-6 level in non-survivors was higher than that in survivors on day 1. IL-10 level in non-survivors was higher than that in survivors on day 1, 2, and 3. IL-6 level in shock patients was higher than that in non-shock patients on day 1, 2, 6 and 7. IL-10 level in shock patients was higher than that in non-shock patients from day 1 to day 7. Plasma time-course curves of IL-6 and IL-10 were different between survivors and non-survivors. Plasma time-course curve of IL-6 was different between patients with shock and without shock. Regression analysis found that IL-6 was correlated with IL-10 and shock. IL-10 was correlated with IL-6 and mortality. Conclusion IL-6 and IL-10 were the key cytokines in the pathogenesis of severe sepsis. IL-6 was comparatively more associated with septic shock and IL-10 was comparatively more associated with mortality.